Readiness and Use of Big Data Analytics in Selected Canadian Higher Education Institutions - Ajanaku, Olateju Jumoke; Ajiferuke, Isola (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2025)
The rapid evolution of information technologies has driven the exponential growth of big data, creating opportunities to leverage data analytics across sectors. In higher education, Big Data Analytics (BDA) holds promise for improving decision-making, enhancing student outcomes, and driving institutional efficiency. However, its implementation remains limited due to technological, organizational, and environmental challenges. This study examines the readiness and use of BDA within selected Canadian higher education institutions, focusing on Southwest Ontario. Utilizing the Technology-Organization-Environment (TOE) framework, the research adopts a qualitative approach, drawing on semi-structured interviews with 10 academic and administrative staff from selected universities in Southwestern Ontario. The result identifies several barriers to BDA readiness and use, including a fragmented data landscape, integration challenges, and resource constraints. The study emphasizes the need for strategic investments in technological infrastructure, leadership engagement, and updated policies to improve BDA adoption. The study concludes with recommendations addressing barriers within the technological, organizational, and environmental contexts to enhance institutional performance and student outcomes.